Fluorine-containing polymer, resin film and photoelectron device

A fluoropolymer with controlled properties addresses depolymerization and thermal decomposition issues in vapor deposition, ensuring stable deposition and precise metal patterning for improved optoelectronic device performance.

JP7619357B2Active Publication Date: 2025-01-22AGC INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2022503658
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-19
Filing Date
2021-02-24
Publication Date
2025-01-22
Estimated Expiration
2041-02-24

AI Technical Summary

Technical Problem

Conventional fluorine-containing polymers used in vapor deposition for organic electroluminescent devices are prone to depolymerization and thermal decomposition, leading to reduced device performance and lifespan due to outgas or partial decomposition products remaining in the conductive film.

Method used

Development of a fluoropolymer with specific properties, including a melting point below 200°C, thermogravimetric reduction rate below 400°C, and a narrow molecular weight distribution, suitable for vapor deposition and metal patterning, using controlled polymerization and molecular weight fractionation techniques.

Benefits of technology

The fluoropolymer ensures stable vapor deposition conditions, prevents depolymerization and thermal decomposition, and allows for precise metal patterning, enhancing the quality and longevity of optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619357000009
    Figure 0007619357000009
  • Figure 0007619357000010
    Figure 0007619357000010
  • Figure 0007619357000011
    Figure 0007619357000011
Patent Text Reader

Abstract

Provided is a fluorine-containing polymer that is suitable for vapor deposition and for metal patterning. Also provided is a resin film that contains such a fluorine-containing polymer as a material. Also provided is an opto-electronic element having such a resin film in the structure thereof. The fluorine-containing polymer satisfies (1)-(3). (1) The melting point is less than 200°C or no melting point is observed. (2) The thermogravimetric reduction rate when the temperature is increased at a heating rate of 2°C / min at a pressure of 1×10-3 Pa reaches essentially 100% at a temperature of at most 400°C. (3) The temperature range from the temperature at which the thermogravimetric reduction rate is 10% to the temperature at which the thermogravimetric reduction rate is 90% when the temperature is increased at a heating rate of 2°C / min at a pressure of 1×10-3 Pa is within 200°C.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fluorine-containing polymer, a resin film, and a photoelectron device. [Background technology]

[0002] Conventionally, organic photoelectron elements such as organic electroluminescence elements (organic EL elements) have been known as light-emitting elements. As a conductive film included in such elements, a conductive film having two types of regions with different light transmittances is known.

[0003] In the following description, of the two regions with different light transmittances, the region with the relatively low light transmittance may be referred to as the "first region" and the region with the high light transmittance as the "second region." Taking an organic EL element as an example, the first region corresponds to, for example, the wiring of the organic EL element, and the second region corresponds to, for example, the cathode layer constituting the organic EL element.

[0004] Patent Document 1 discloses a method for producing the above-mentioned conductive film, in which a pattern film is first formed from a material that suppresses the formation of a metal film, and then a metal film is formed on top of the pattern film by vapor deposition, sputtering, or the like. Specifically, the method described in Patent Document 1 lists poly tetrafluoroethylene (PTFE) as an example of the "material that suppresses the formation of a metal film." According to the above-mentioned method, a metal film is formed avoiding the pre-formed pattern film. As a result, a second region with high light transmittance is formed in the region where the pattern film is formed with the material that suppresses the formation of a metal film. Also, a large amount of metal is formed in the region where the pattern film is not formed, forming a first region with relatively low light transmittance, and a conductive film with each region formed is obtained. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] U.S. Patent No. 10270033 Summary of the Invention [Problem to be solved by the invention]

[0006] Known fluorine-containing polymers such as those described in Patent Document 1 are prone to depolymerization or thermal decomposition during vapor deposition. Furthermore, when outgassing or partial decomposition products generated by such depolymerization or thermal decomposition remain in the conductive film, there is a risk of deteriorating the device performance or device life of an organic EL device having the conductive film. The above-mentioned problems are not limited to the manufacturing process of organic EL elements. When a process includes a step of depositing a fluororesin, the same problems may occur in display elements, photoelectron elements, and organic light-emitting elements.

[0007] The present invention has been made in view of the above circumstances, and has an object to provide a fluorine-containing polymer that is suitable for vapor deposition and can be suitably patterned with metal. Another object is to provide a resin film that contains such a fluorine-containing polymer as a material. Another object is to provide a photoelectron device having such a resin film in its structure. [Means for solving the problem]

[0008] In order to solve the above problems, one aspect of the present invention includes the following aspects. [1] A fluorine-containing polymer that satisfies the following (1) to (3): (1) The melting point is less than 200°C or no melting point is observed. (2) 1×10 -3 (3) When heated at a rate of 2°C / min under a pressure of 1×10 Pa, the thermal weight loss rate reaches substantially 100% at 400°C or less. -3 When the temperature is increased at a rate of 2°C / min under a pressure of 10 Pa, the temperature range from the temperature at which the thermal weight loss rate becomes 10% to the temperature at which it becomes 90% is within 200°C. [2] Storage modulus at 40°C is 4×10 7 The fluorine-containing polymer according to [1], wherein the molecular weight is less than 100 Pa. [3] The fluorine-containing polymer according to [1] or [2], which has a unit derived from a fluoroolefin. [4] The fluorine-containing polymer according to [3], which has at least a unit derived from tetrafluoroethylene.

[0009] [5] The fluorine-containing polymer according to [3] or [4], which has a unit derived from a perfluoroalkyl vinyl ether. [6] The fluorine-containing polymer according to [5], wherein the perfluoroalkyl vinyl ether is perfluoropropyl vinyl ether. [7] The fluorine-containing polymer according to [6], wherein a content of the units derived from perfluoropropyl vinyl ether based on all units is 11 mol % or more. [8] The fluorine-containing polymer according to [3] or [4], further having a unit derived from hexafluoropropylene. [9] The fluoropolymer according to [8], wherein the content of the units derived from hexafluoropropylene based on all units is 18 mol % or more.

[10] The fluorine-containing polymer according to any one of [1] to [9], which has a trifluoromethyl moiety and has a content of the trifluoromethyl moiety of 0.1 mmol / g or more.

[0010]

[11] A resin film made of the fluorine-containing polymer according to any one of [1] to

[10] above.

[12] An optoelectronic device having the resin film according to

[11] above. Effect of the Invention

[0011] According to the present invention, it is possible to provide a fluorine-containing polymer that is suitable for vapor deposition and can be suitably patterned by metal. It is also possible to provide a resin film that contains such a fluorine-containing polymer as a material. It is also possible to provide a photoelectron device having such a resin film in its structure. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic diagram illustrating requirements (2) and (3). [Diagram 2] FIG. 2 is a plan view of the conductive film 1. As shown in FIG. [Diagram 3]FIG. 3 is a cross-sectional view taken along line III-III in FIG. [Figure 4] FIG. 4 is a schematic diagram showing a method for producing the conductive film 1. As shown in FIG. [Diagram 5] FIG. 5 is a schematic diagram showing a method for producing the conductive film 1. As shown in FIG. [Figure 6] FIG. 6 is a schematic diagram showing a method for producing the conductive film 1. As shown in FIG. [Figure 7] FIG. 7 is a cross-sectional view showing a schematic view of an optoelectronic device (organic EL device) 100 according to the second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In this specification, the term "unit" constituting a polymer means a portion derived from one monomer molecule (i.e., a monomer unit) that exists in the polymer and constitutes the polymer. Hereinafter, a unit derived from an individual monomer may be referred to by the name of the monomer followed by "unit."

[0014] As used herein, the "main chain" of a polymer refers to a carbon atom chain formed by addition polymerization of a monomer having a carbon-carbon unsaturated double bond, and composed of carbon atoms that constituted the carbon-carbon unsaturated double bond in the monomer.

[0015] The term "reactive functional group" means a group having reactivity that can form a bond when heated or the like, by reacting (excluding radical reactions) between molecules of the fluoropolymer or with other components blended together with the fluoropolymer.

[0016] In the present specification, the term "aliphatic ring" refers not only to a carbon ring structure whose ring skeleton is composed only of carbon atoms, but also to a heterocyclic ring structure whose ring skeleton contains an atom other than carbon atoms (heteroatom). Examples of the heteroatom include an oxygen atom, a nitrogen atom, and a sulfur atom.

[0017] [First embodiment] The fluoropolymer and resin film according to the first embodiment of the present invention will be described below with reference to Figures 1 to 6. In all the following figures, the dimensions and ratios of the components are appropriately changed to make the figures easier to see.

[0018] (Fluorine-containing polymer) The fluoropolymer of the present embodiment satisfies the following requirements (1) to (3). Requirement (1) The melting point is less than 200°C, or no melting point is observed. Requirement (2) 1×10 -3 When the temperature is increased at a rate of 2°C / min under a pressure of 10 Pa, the thermal weight loss rate reaches substantially 100% at 400°C or lower. Requirement (3) 1×10 -3 When the temperature is increased at a rate of 2°C / min under a pressure of 10 Pa, the temperature range from the temperature at which the thermal weight loss rate becomes 10% to the temperature at which it becomes 90% is within 200°C.

[0019] The fluoropolymer satisfying the above requirements (1) to (3) has properties suitable for deposition and can be suitably formed into a deposited film. Furthermore, when the obtained deposited film is used for patterning a metal film, the patterning of the metal film becomes easy. The following explains each in order.

[0020] (Requirement (1)) The fluoropolymer of this embodiment has a melting point of less than 200°C, or no melting point is observed. The fluoropolymer has a melting point which is preferably observed and is within a predetermined range. When the melting point of the fluoropolymer is observed, the melting point of the fluoropolymer is preferably 190°C or lower, more preferably 180°C or lower. The lower limit of the melting point is not particularly limited, but is preferably 100°C or higher in order to easily maintain the shape of the film made of the fluoropolymer.

[0021] In this embodiment, the melting point is a value measured using a differential scanning calorimeter (for example, DSC 204 F1 Phoenix manufactured by NETZSCH). Specifically, 9 mg of the fluoropolymer is placed in a sample container, and the heat capacity is measured when the temperature is raised from -70°C to 350°C at 10°C per minute, and the melting point is determined from the obtained melting peak.

[0022] A fluoropolymer having the above-mentioned melting point can be judged to have low crystallinity. When a metal material is vapor-deposited on a resin film made of a fluoropolymer, if the resin film contains a large amount of fluoropolymer crystals, the grain boundaries (interfaces) of the fluoropolymer crystals become the starting points for nucleation of the vapor-deposited material (metal), and a metal film is easily formed on the resin film. Conversely, if the resin film contains a small amount of fluoropolymer crystals, a metal film is difficult to form on the resin film.

[0023] In other words, the lower the crystallinity of a fluoropolymer that satisfies requirement (1), the more difficult it is to form a metal film on a resin film made of the fluoropolymer, and the easier it is to pattern a metal film due to the difference between the surrounding resin film on which a metal film is relatively easily formed and the surrounding resin film.

[0024] For example, when a fluoropolymer has units (PPVE units) derived from perfluoropropyl vinyl ether (PPVE), an increase in the content of PPVE units decreases the crystallinity of the fluoropolymer and at the same time decreases the melting point. Furthermore, when the fluoropolymer has an aliphatic ring structure in the main chain, the aliphatic ring structure is likely to lose crystallinity, and therefore the fluoropolymer has low crystallinity or is amorphous. When the fluoropolymer is amorphous, no melting point is observed.

[0025] (Requirement (2)) In the following explanation, "fluorine-containing polymer 1 × 10 -3 The temperature at which the thermal weight loss rate reaches substantially 100% when heated at a rate of 2°C / min under a pressure of 10 Pa is sometimes referred to as the "100% thermal weight loss temperature" (°C). Requirement (2) specifies that the 100% thermal weight loss temperature is 400°C or lower.

[0026] In this embodiment, the thermal weight loss rate of the fluoropolymer is a value measured using a vacuum differential thermobalance (VPE-9000, manufactured by Advance Riko Co., Ltd.). -3 The weight loss rate (%) of the fluoropolymer relative to its initial weight (50 mg) is measured when the temperature is raised from room temperature to 500° C. at a rate of 2° C. per minute under a vacuum of 100 Pa.

[0027] The term "substantially" in requirement (2) means that when the thermal weight loss rate is measured under the above-mentioned conditions, the thermal weight loss is below the lower detection limit in the temperature range of 400°C or less, and no thermal weight loss can be confirmed.

[0028] It can be said that the lower the temperature at which the fluoropolymer of this embodiment satisfies the above requirement (2), the lower the molecular weight (degree of polymerization). If a fluoropolymer not satisfying the above requirement (2) is to be vapor-deposited, it will be necessary to heat it to a temperature exceeding 400°C. On the other hand, if it is heated to a temperature range exceeding 400°C, the high temperature may cause the fluoropolymer to depolymerize or pyrolyze. In that case, the products generated by the depolymerization or pyrolysis may increase the internal pressure of the vacuum chamber used for vapor deposition. If the internal pressure of the vacuum chamber increases in this way, the vapor deposition conditions become unstable, and the quality of the obtained vapor-deposited film (resin film) may be unstable.

[0029] Furthermore, when a fluoropolymer not satisfying the above requirement (2) is heated at a temperature exceeding 400°C, partially depolymerized or thermally decomposed fluoropolymer having a small molecular weight may be mixed into the resin film, possibly reducing the heat resistance of the resin film. Furthermore, when a fluoropolymer not satisfying the above requirement (2) is heated at a temperature exceeding 400°C, the fluoropolymer having unstable terminals produced by depolymerization or thermal decomposition may be mixed into the resin film, possibly impairing the quality of the resin film and the element containing the resin film.

[0030] On the other hand, when the fluoropolymer satisfying the above requirement (2) is used as a material for deposition under vacuum, it can be suitably deposited by heating at a temperature of 400° C. or less, which allows deposition under stable deposition conditions without the risk of the above-mentioned depolymerization or thermal decomposition.

[0031] The fluorine-containing polymer of this embodiment is 1×10 -3 It is preferable that the thermal weight loss rate when heated at a heating rate of 2°C / min under a pressure of 10 Pa reaches substantially 100% at a temperature of 350°C or lower, i.e., the temperature at which the thermal weight loss rate reaches substantially 100% is 350°C or lower.

[0032] (Requirement (3)) In the following explanation, "fluorine-containing polymer 1 × 10 -3 The temperature range from the temperature at which the thermal weight loss rate is 10% to the temperature at which it is 90% when the temperature is increased at a rate of 2°C / min under a pressure of 100 Pa is sometimes referred to as the "thermal weight loss temperature range" (°C). Requirement (3) stipulates that the thermal weight loss temperature range is within 200°C.

[0033] It can be said that the narrower the temperature range in which the fluoropolymer of this embodiment satisfies the above requirement (3), the narrower the molecular weight distribution. If a resin film is produced using a fluoropolymer that does not satisfy the above requirement (3), there will be a large difference between the molecular weight of the fluoropolymer deposited at the beginning of deposition and the molecular weight of the fluoropolymer deposited at the end of deposition, and the molecular weight of the fluoropolymer will vary in the thickness direction of the same resin film, which could result in unstable physical properties of the resin film. Furthermore, when resin films are produced continuously under the same conditions, if a fluoropolymer not satisfying the above requirement (3) is used, the quality of the produced resin films may vary between lots. Furthermore, the low molecular weight substance contained in the fluorine-containing polymer may be generated as outgas during deposition and adhere to the inside of a vacuum chamber, thereby contaminating the vacuum chamber. For example, in the process of producing an optoelectronic device, such a contamination source may cause a reduction in the life span of the device or a short circuit, thereby seriously impairing the quality of the device.

[0034] On the other hand, in the case of a fluoropolymer satisfying the above requirement (3), the difference between the molecular weight of the fluoropolymer deposited at the beginning of deposition and that of the fluoropolymer deposited at the end of deposition is small, and the change in the molecular weight of the fluoropolymer in the thickness direction of the resin film is small. Therefore, the physical properties of the obtained resin film are likely to be stable. Furthermore, when resin films are continuously produced under the same conditions, the quality variation between lots of the produced resin films can be suppressed. Furthermore, since it does not contain low molecular weight substances that cause outgassing, there is no risk of contamination of the deposition chamber. Methods for obtaining a fluorine-containing polymer having a narrow molecular weight distribution that satisfies the above requirement (3) include molecular weight adjustment by controlled polymerization such as living radical polymerization, and molecular weight fractionation by sublimation purification, supercritical extraction, and size exclusion chromatography.

[0035] Fig. 1 is a schematic diagram illustrating requirements (2) and (3), and is a graph showing the relationship between the measurement temperature and the thermal weight loss rate. The horizontal axis of Fig. 1 is the measurement temperature (unit: °C), and the vertical axis is the thermal weight loss rate (unit: %). In Fig. 1, the behavior of a fluoropolymer that satisfies requirements (2) and (3) is indicated by the symbol P, and the behavior of a fluoropolymer that does not satisfy requirements (2) and (3) is indicated by the symbol Px.

[0036] In Fig. 1, graph P showing the behavior of the fluoropolymer of this embodiment reaches 100% in thermal weight loss at a temperature (Td100) lower than 400°C. In contrast, graph Px showing the behavior of a fluoropolymer not satisfying requirements (2) and (3) does not reach 100% in thermal weight loss at 400°C. In addition, in FIG. 1, graph P showing the behavior of the fluoropolymer of this embodiment has a Td90-Td10 value W of 200° C. or less. It is clear from FIG. 1 that the fluoropolymer of this embodiment undergoes a steep thermal weight loss between the temperature Td10 and the temperature Td90.

[0037] The occurrence of depolymerization, thermal decomposition and outgassing during deposition of the fluoropolymer can be evaluated as follows, taking note of the change in the internal pressure of the vacuum chamber. (Method for evaluating chamber pressure changes during deposition) 0.1 g of fluoropolymer was charged into the vacuum deposition machine, and the pressure in the chamber was increased to 10 -4 After reducing the pressure to below Pa, a fluorine-containing polymer is deposited to a thickness of 200 nm at a deposition rate of 0.1 nm / sec. During this process, the pressure inside the chamber is monitored and the maximum pressure during deposition is measured. A fluoropolymer having a chamber pressure increase rate of 10 times or less, calculated using the following formula, is less susceptible to depolymerization, thermal decomposition and outgassing, and can be suitably deposited. Chamber pressure increase rate during deposition = Maximum pressure during deposition / Initial pressure before deposition Fluorine-containing polymers with an increase rate of more than 10 times are judged to be unsuitable for deposition because of the large amount of depolymerization, thermal decomposition, and outgassing.

[0038] (Molecular weight fraction) When a fluoropolymer to be used does not satisfy the above requirements (2) and (3), it can be made into the fluoropolymer of the present embodiment which satisfies the above requirements (2) and (3) by molecular weight fractionation of the fluoropolymer.

[0039] A fluoropolymer satisfying the above requirements (2) and (3) can be obtained by molecular weight fractionation of a polymer. In the following description, the polymer to be subjected to molecular weight fractionation may be referred to as a "raw polymer." Examples of the molecular weight fractionation method include sublimation purification, supercritical extraction, and size exclusion chromatography to fractionate the molecular weight and prepare a polymer that satisfies the requirements (2) and (3).

[0040] (sublimation purification) Sublimation purification is a technique in which the target compound is separated and recovered as a solid by utilizing the precipitation temperature difference of compounds contained in the gaseous target compound after heating the target compound (raw polymer) under reduced pressure to sublimate or evaporate a part or all of the target compound. This type of sublimation purification can be performed using a sublimation purification device that has a feed section for feeding the target compound and a collection section for separating the target compound in the gaseous state according to its precipitation temperature and collecting it as a solid, and that can maintain a high degree of vacuum. The structure of the sublimation purification apparatus is not particularly limited, but for example, a so-called Mill-type sublimation purification apparatus consisting of a glass cooling tube, a flask-shaped glass container surrounding the cooling tube, and a vacuum exhaust device for reducing the pressure inside the glass container can be used. Also, as the sublimation purification apparatus, a glass tube-type sublimation purification apparatus including a cylindrical glass sublimation tube, a heating device for accommodating the sublimation tube inside and heating the sublimation tube, and a high vacuum exhaust device for reducing the pressure inside the sublimation tube can be used. Hereinafter, the sublimation purification of a fluoropolymer and the method of molecular weight fractionation by sublimation purification will be described taking a glass tube type sublimation purification apparatus as an example.

[0041] In the sublimation purification of fluoropolymers, the raw polymer is charged into the sublimation tube, and the pressure is reduced to, for example, 1×10 -3 After increasing the degree of vacuum in the sublimation tube to 0.1 Pa or less, the feed section is heated using a heating device, whereby the fluorine-containing polymer contained in the raw polymer is sublimated or evaporated. In the sublimation tube, the region on the side of the feed section that is exhausted by the high vacuum exhaust device corresponds to the "collection section." The collection section is set at a temperature lower than the heating temperature of the feed section. The fluoropolymer sublimated or evaporated from the raw material polymer in the feed section is precipitated and solidified on the wall surface of the collection section, or liquefied on the wall surface of the collection section, and collected.

[0042] The collection temperature of the collection section corresponds to the temperature at which the fluoropolymer sublimes from a gas to a solid (precipitates) or the temperature at which the fluoropolymer coagulates from a gas to a liquid, and corresponds to the molecular weight of the fluoropolymer. By providing a plurality of collection sections with different collection temperatures in the sublimation tube, the raw material polymer can be fractionated into fluoropolymers with different molecular weights. Specifically, for example, when the feed section is heated to A°C and the collection section is heated to B°C and C°C from the side closer to the feed section (A>B>C), the collection section set at B°C collects a fluoropolymer in a molecular weight range that is in a gaseous state at A°C and a solid (or liquid) at B°C. Similarly, the collection section set at C° C. collects a fluoropolymer in a molecular weight range that is gaseous at B° C. and solid (or liquid) at C° C. That is, the collection section set at C° C. collects, among the fluoropolymers contained in the raw material polymer, a fluoropolymer in the collection temperature range B° C.-C° C. that is gaseous at B° C. and solid (or liquid) at C° C.

[0043] The above-mentioned requirement (3) can be satisfied by controlling the collection temperature range as described above, for example, by collecting in a collection section having a collection temperature range of 200° C. The collected fluoropolymer is checked to see whether it satisfies requirement (3), and if it does not, the temperature conditions of the collection section are controlled to narrow the collection temperature range. In the collection section, the lower the set temperature of the fluoropolymer collected, the lower the concentration of fluoropolymers collected. -3 The temperature at which the thermal weight loss rate under a pressure of 100 Pa reaches 100% is low, that is, the molecular weight of the fluoropolymer is small.

[0044] The collection temperature range is preferably 200° C. or less, more preferably 100° C. or less, and even more preferably 50° C. or less. The smaller the collection temperature range, the less the fluctuation in the deposition conditions becomes, and the more likely it is that the quality of the resin film will be stable.

[0045] As long as the molecular weight fractionated fluoropolymer satisfies the requirements (2) and (3), a plurality of fluoropolymers having different collection temperature ranges may be mixed.

[0046] (Supercritical extraction) Supercritical extraction is a technique for obtaining an extract by utilizing the high solubility and diffusivity of a supercritical fluid. For example, supercritical CO2 is used as the supercritical fluid, and a relatively low molecular weight fluorine-containing polymer is dissolved in the supercritical CO2 to obtain an extract. Furthermore, by using a fluorine-containing solvent as an additive (entrainer) for the supercritical fluid, the solubility of the fluorine-containing polymer in the supercritical fluid can be increased.

[0047] The fluorine-containing solvent used as the entrainer is not particularly limited. For example, the fluorinophilic parameter P F A fluorine-containing solvent in which is 1 or more is preferred. (Fluorophilic parameter P F ) 30 μL of the fluorine-containing solvent is dropped into a two-phase system of 3 g of toluene and 3 g of perfluoromethylcyclohexane, mixed thoroughly, and allowed to stand overnight, and then the fluorine-containing solvent contained in the toluene and the fluorine-containing solvent contained in the perfluoromethylcyclohexane are measured by gas chromatography. The concentration (unit: mL / L) of the fluorine-containing solvent in the toluene is expressed as M P The concentration of the fluorine-containing solvent in the perfluoromethylcyclohexane (unit: mL / L) is M F When the above formula is used, the fluorine-philic parameter P is calculated by the following formula (A). F Let us assume that. P F =M F / M P …(A)

[0048] Examples of the fluorine-containing solvent used as an entrainer include the following compounds.

[0049] 1,1,1,2,2,3,3,4,4,5,5,6,6-Tridecafluorohexane (AC-2000, manufactured by AGC) (P F =12) 1,1,1,2,2,3,3,4,4,5,5,6,6-Tridecafluorooctane (AC-6000, manufactured by AGC) (P F =5.6) Cytop CT-SOLV100E (AGC) (P F =8.2) Cytop CT-SOLV180 (AGC) (P F =∞) HFE7300 (manufactured by 3M) (P F =8.2) 1,1,1,2,2,3,4,5,5,5-Decafluoropentane (Vertre XF, manufactured by Chemours) (P F =3.7) 1H,1H,2H,2H-Perfluorooctanol (P F =1.1) 1,1,2,2-Tetrafluoroethyl-2,2,2-trifluoroethyl ether (AE-3000, manufactured by AGC) (P F =0.6) HCFC-225ca / HCFC-225cb(45 / 55)(P F =0.3) Perfluorobenzene (P F =0.3) Hexafluoro-2-propanol (P F =0.24) 1H,1H,7H-Perfluoroheptanol (P F =0.23) 1H,1H,5H-Perfluoropentanol (P F =0.1)

[0050] The extraction process can be carried out, for example, using supercritical CO2 under conditions of an extraction pressure of 7.4 MPa or higher and an extraction temperature of 31°C or higher. The extraction pressure is preferably 30 MPa or more, more preferably 50 MPa or more, and even more preferably 70 MPa or more. There is no particular limit to the upper limit of the extraction pressure, but it is preferably 100 MPa or less. The upper limit and lower limit of the extraction pressure can be combined in any way. The extraction temperature is preferably 40° C. or higher, and more preferably 80° C. or higher. The extraction temperature is preferably 300° C. or lower, more preferably 200° C. or lower, and even more preferably 100° C. or lower. The upper and lower limit values ​​of the extraction temperature can be combined in any manner. Within the above range, the desired molecular weight fractionation of the fluoropolymer can be carried out efficiently.

[0051] Molecular weight fractionation is also useful for the purpose of removing residual foreign matter such as initiators, chain transfer agents, solvents, by-products, etc., used in the polymerization process of the fluoropolymer. Since such residual foreign matter is generated as outgas during deposition and may adhere to the inside of the vacuum chamber and contaminate the vacuum chamber, it is more preferable to carry out sublimation purification or supercritical extraction even when requirements (2) and (3) are met. As long as the molecular weight fractionated fluoropolymer satisfies the requirements (2) and (3), a plurality of fluoropolymers extracted under different conditions may be mixed.

[0052] (Other requirements) The fluoropolymer of the present embodiment preferably satisfies the following requirement (4). Requirement (4) Storage modulus at 25°C is 4 x 10 7 Less than Pa. A fluoropolymer satisfying the above requirement (4) is highly flexible and has excellent followability when the shape is changed. Therefore, when a fluoropolymer satisfying the requirement (4) is used as the material of a resin film of a bendable device, the resin film relieves the shear stress generated when the device is bent at the interface with the layer in contact with the resin film. This is expected to suppress damage to the device when it is bent. An example of the bendable device is a foldable display.

[0053] In addition, a fluoropolymer that satisfies requirement (4) has a low melt viscosity. Therefore, when used as a deposition material, a fluoropolymer that satisfies requirement (4) has a low viscosity under heating, which facilitates surface renewal of the material by convection, thereby enabling excellent deposition stability to be obtained. Furthermore, this surface renewal by convection suppresses partial overheating of the deposition material, making it possible to avoid thermal decomposition due to excessive heating.

[0054] A fluoropolymer satisfying the above requirement (4) can be obtained, for example, by changing the content of PPVE units in the fluoropolymer. As the content of PPVE units increases, the storage modulus tends to decrease. Similarly, a fluorine-containing polymer satisfying the above requirement (4) can be obtained, for example, by changing the content of units (HFP units) derived from hexafluoropropylene (HFP) contained in the fluorine-containing polymer. As the content of HFP units increases, the storage modulus tends to decrease.

[0055] In this embodiment, the storage modulus is a value measured using a dynamic viscoelasticity measuring device (e.g., MCR502, manufactured by Anton Paar) and a heating furnace for viscoelasticity measuring devices (e.g., CTD450, manufactured by Anton Paar). Specifically, a sample (fluoropolymer) is heated to above its melting point, and then cooled at 2°C / min in a constant temperature reduction mode. Using the above measuring device, the storage modulus (G') is measured under conditions of a strain of 0.01% and a frequency of 1 Hz.

[0056] (Fluorine-containing polymer structure) The fluoropolymer of this embodiment is not particularly limited in terms of the units constituting the polymer, so long as it satisfies the above requirements (1) to (3).

[0057] The fluorine atom content of the fluorine-containing polymer is preferably 20% by mass or more, more preferably 40% by mass or more, even more preferably 60% by mass or more, and particularly preferably 70% by mass or more. The higher the fluorine atom content, the lower the surface energy of the resin film made of the fluorine-containing polymer, making it difficult to form a metal film on the surface of the resin film. Therefore, if a fluorine-containing polymer having the above fluorine atom content is used, it is easy to pattern the metal film.

[0058] The fluorine atom content (mass %) is calculated by the following formula. (Fluorine atom content) = [19 x NF / MA] x 100 NF: the sum of the values ​​obtained by multiplying the total atomic weight of fluorine atoms constituting each type of unit constituting a fluorine-containing polymer by the molar ratio of that unit to all units. MA: the sum of the values ​​obtained by multiplying the total atomic weight of all atoms constituting the unit by the molar ratio of the unit to all units for each type of unit constituting the fluorine-containing polymer. The above NF and MA are 1 H-NMR, 19 The NF and MA can be calculated from the molar ratio and terminal amount of the structural units of the fluoropolymer obtained by F-NMR, elemental analysis, and IR. In addition, the NF and MA can also be calculated from the charged amounts of the monomers and initiator used in the production of the fluoropolymer.

[0059] The fluorine-containing polymer preferably contains a trifluoromethyl moiety. The "trifluoromethyl moiety" refers to CF3-. The trifluoromethyl moiety includes not only a trifluoromethyl group, but also a part of a substituent such as CF3- contained in a pentafluoroethyl group. The content of trifluoromethyl moiety is preferably 0.1 mmol / g or more, more preferably 0.3 mmol / g or more, and even more preferably 0.6 mmol / g or more. The higher the content of trifluoromethyl moiety, the lower the surface energy of the resin film made of the fluorine-containing polymer. This makes it difficult to form a metal film on the surface of the resin film, and makes it easier to pattern the metal film.

[0060] The content (mmol / g) of trifluoromethyl moieties can be calculated by the following formula. (Trifluoromethyl moiety content) = [NCF3 / MA] x 1000 NCF3: the sum of values ​​obtained by multiplying the number of moles of trifluoromethyl moieties constituting the units by the molar ratio of the units to all units for each type of unit constituting the fluorinated polymer. MA: the sum of the values ​​obtained by multiplying the total atomic weight of all atoms constituting the unit by the molar ratio of the unit to all units for each type of unit constituting the fluorine-containing polymer. The above NCF3 and MA are 1 H-NMR, 19 NCF3 and MA can be calculated from the molar ratio and terminal amount of the structural units of the fluoropolymer obtained by F-NMR, elemental analysis, and IR. NCF3 and MA can also be calculated from the amounts of monomers and initiators used in the production of the fluoropolymer.

[0061] As the fluorine-containing polymer, the following polymer (1) and polymer (2) are preferred. Polymer (1): A fluorine-containing polymer having no aliphatic ring in the main chain and having a fluoroolefin unit. Polymer (2): A fluorine-containing polymer having an aliphatic ring in the main chain. In the present invention, as the fluorine-containing polymer, either one of the polymers (1) and (2) may be used alone, or the polymers (1) and (2) may be used in combination.

[0062] <Polymer (1)> The polymer (1) may be a homopolymer of a fluoroolefin, a copolymer of two or more kinds of fluoroolefins, or a copolymer of a fluoroolefin and another monomer copolymerizable with the fluoroolefin.

[0063] Examples of the fluoroolefin include perfluoroolefins such as tetrafluoroethylene (TFE) and hexafluoropropylene (HFP), and perfluoroalkyl vinyl ethers such as perfluoromethyl vinyl ether (PMVE), perfluoroethyl vinyl ether (PEVE), and perfluoropropyl vinyl ether (PPVE).

[0064] Further, the fluoroolefin may include fluoroolefins having hydrogen atoms or chlorine atoms, such as chlorotrifluoroethylene (CTFE), trifluoroethylene (TrFE), vinylidene fluoride (VdF), 1,2-difluoroethylene, and 1-fluoroethylene.

[0065] Examples of other monomers copolymerizable with fluoroolefins include olefins such as ethylene and propylene, aromatic vinyl compounds such as vinyl ethers, vinyl esters and styrene, allyl compounds such as allyl ethers, acryloyl compounds, and methacryloyl compounds. Also usable are fluorine-containing monomers having a perfluoroalkyl group or a perfluoropolyether group, such as vinyl ethers, vinyl esters, aromatic vinyl compounds, allyl compounds, acryloyl compounds and methacryloyl compounds.

[0066] In particular, the polymer (1) preferably has a perfluoroalkyl vinyl ether unit. More specifically, the fluorine-containing polymer preferably has a PPVE unit.

[0067] The crystallinity of polymer (1) changes as the content of the PPVE unit changes. Specifically, as the content of the PPVE unit in the fluoropolymer increases, the crystallinity of the fluoropolymer decreases. The content of the PPVE unit is preferably 11 mol% or more, more preferably 12 mol% or more, and even more preferably 14 mol%, based on the total number of moles of all monomer units constituting the fluoropolymer. The content of the PPVE unit is preferably 25 mol% or less, based on the total number of moles of all monomer units constituting the fluoropolymer. When the content of the PPVE unit is within the above range, the melting point of the fluoropolymer satisfies the requirement (1), and deposition becomes possible in a favorable manner.

[0068] In addition, the polymer (1) preferably has an HFP unit. The crystallinity of the polymer (1) changes when the content of the HFP unit changes. Specifically, when the content of the HFP unit in the fluoropolymer increases, the crystallinity of the fluoropolymer decreases.

[0069] The content of HFP units is preferably 18 mol% or more, more preferably 20 mol%, based on the total number of moles of all monomer units constituting the fluoropolymer, and is preferably 25 mol% or less, based on the total number of moles of all monomer units constituting the fluoropolymer. When the content of HFP units is within the above range, the melting point of the fluorine-containing polymer satisfies the requirement (1), and deposition becomes possible in a favorable manner.

[0070] When the polymer (1) is a copolymer, the content of the fluoroolefin unit is preferably 20 mol % or more, more preferably 40 mol % or more, and even more preferably 80 mol % or more.

[0071] As the polymer (1), a synthesized product or a commercially available product may be used. Examples of the polymer (1) include the following polymers. Polytetrafluoroethylene (PTFE) Tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer (PFA) Tetrafluoroethylene / hexafluoropropylene copolymer (FEP) Tetrafluoroethylene / perfluoro(alkyl vinyl ether) / hexafluoropropylene copolymer (EPA) Ethylene / Tetrafluoroethylene Copolymer (ETFE) Polyvinylidene fluoride (PVDF) Polyvinyl fluoride (PVF) Polychlorotrifluoroethylene (PCTFE) Ethylene / chlorotrifluoroethylene copolymer (ECTFE)

[0072] Among these, polymers in which all hydrogen atoms bonded to carbon atoms are substituted with fluorine are preferred, since it is difficult to form a metal film on the surface of a film made of a fluorine-containing polymer and patterning is easy. That is, PTFE, PFA, FEP, and EPA are preferred.

[0073] The polymer (1) can be produced by a known method. As the polymer (1), a synthesized product or a commercially available product may be used.

[0074] <Polymer (2)> The polymer (2) is a fluorine-containing polymer having an aliphatic ring in the main chain. The term "fluoropolymer having an aliphatic ring in the main chain" means that the fluoropolymer has a unit having an aliphatic ring structure, and at least one of the carbon atoms constituting the aliphatic ring is a carbon atom constituting the main chain. The aliphatic ring may be a ring having a heteroatom such as an oxygen atom.

[0075] The "main chain" of a polymer refers to the chain of carbon atoms derived from the two carbon atoms that constitute the polymerizable double bond in the case of a monoene polymer. In the case of a cyclopolymerizable diene cyclopolymer, it refers to a chain of carbon atoms derived from four carbon atoms constituting two polymerizable double bonds. Furthermore, in a copolymer of a monoene and a cyclopolymerizable diene, it refers to a chain of carbon atoms derived from the above two carbon atoms of the monoene and the above four carbon atoms of the diene.

[0076] When the monoene has a polymerizable double bond between one carbon atom constituting the ring structure of the aliphatic ring and an exocyclic carbon atom, the main chain of the polymer having the aliphatic ring in the main chain has one carbon atom constituting the ring structure that previously constituted the polymerizable double bond of the monoene. When the monoene has a polymerizable double bond between two adjacent carbon atoms constituting the ring structure of the aliphatic ring, the main chain of the polymer having the aliphatic ring in the main chain has two carbon atoms constituting the ring structure that previously constituted the polymerizable double bond of the monoene. In the case of the above-mentioned cyclopolymerizable diene, the main chain of the polymer having an aliphatic ring in the main chain is composed of four carbon atoms which constituted the two polymerizable double bonds of the diene, and two to four of the four carbon atoms constitute the ring skeleton of the aliphatic ring.

[0077] The number of atoms constituting the ring skeleton of the aliphatic ring in the polymer (2) is preferably 4 to 7, and more preferably 5 to 6. That is, the aliphatic ring is preferably a 4- to 7-membered ring, and more preferably a 5- or 6-membered ring. When the aliphatic ring has a heteroatom as an atom constituting the ring, examples of the heteroatom include an oxygen atom and a nitrogen atom, and an oxygen atom is preferred. The number of heteroatoms constituting the ring is preferably 1 to 3, and more preferably 1 or 2. The aliphatic ring may or may not have a substituent. The term "optionally having a substituent" means that a substituent may be bonded to an atom constituting the ring skeleton of the aliphatic ring.

[0078] The hydrogen atoms bonded to the carbon atoms constituting the aliphatic ring of the polymer (2) are preferably substituted with fluorine atoms. In addition, when the aliphatic ring has a substituent, and when the substituent has a hydrogen atom bonded to a carbon atom, the hydrogen atom is preferably substituted with a fluorine atom. Examples of the substituent having a fluorine atom include a perfluoroalkyl group, a perfluoroalkoxy group, and =CF2. The aliphatic ring in the polymer (2) is preferably a perfluoroaliphatic ring (an aliphatic ring in which all of the hydrogen atoms bonded to carbon atoms, including the substituents, are substituted with fluorine atoms).

[0079] Examples of the polymer (2) include the following polymers (21) and (22). Polymer (21): a fluorine-containing polymer having a unit derived from a cyclic fluorine-containing monoene. Polymer (22): A fluorine-containing polymer having units formed by cyclopolymerization of a fluorine-containing diene capable of cyclopolymerization (hereinafter also simply referred to as "fluorine-containing diene").

[0080] Polymer (21): The "fluorine-containing cyclic monoene" refers to a fluorine-containing monomer having one polymerizable double bond between carbon atoms constituting an aliphatic ring, or a fluorine-containing monomer having one polymerizable double bond between a carbon atom constituting an aliphatic ring and a carbon atom outside the aliphatic ring. As the fluorine-containing cyclic monoene, the following compound (1) or compound (2) is preferable. [ka] [where, X 1 , X 2 , X 3 , X 4 , Y 1 and Y 2 are each independently a fluorine atom, a perfluoroalkyl group which may contain an ethereal oxygen atom (-O-), or a perfluoroalkoxy group which may contain an ethereal oxygen atom. 3 and X 4 may be bonded to each other to form a ring.

[0081] X 1 , X 2 , X 3 , X 4 , Y 1 and Y 2 The perfluoroalkyl group in the formula (I) preferably has 1 to 7 carbon atoms, and more preferably has 1 to 4 carbon atoms. The perfluoroalkyl group is preferably linear or branched, and more preferably linear. Specific examples of the perfluoroalkyl group include a trifluoromethyl group, a pentafluoroethyl group, and a heptafluoropropyl group, and the trifluoromethyl group is particularly preferred. X 1 , X 2 , X 3 , X 4 , Y 1 and Y 2 The perfluoroalkoxy group in the above formula includes the above perfluoroalkyl group to which an oxygen atom (-O-) is bonded, and a trifluoromethoxy group is particularly preferred.

[0082] In formula (1), X 1 is preferably a fluorine atom. X 2 is preferably a fluorine atom, a trifluoromethyl group, or a perfluoroalkoxy group having 1 to 4 carbon atoms, and particularly preferably a fluorine atom or a trifluoromethoxy group. X 3 and X 4 are each independently preferably a fluorine atom or a perfluoroalkyl group having 1 to 4 carbon atoms, and particularly preferably a fluorine atom or a trifluoromethyl group. X 3 and X 4 may be bonded to each other to form a ring. The number of atoms constituting the ring skeleton of the ring is preferably 4 to 7, and particularly preferably 5 to 6.

[0083] Preferred specific examples of the compound (1) include the compounds (1-1) to (1-5). [ka]

[0084] In formula (2), Y 1 and Y 2 are each independently preferably a fluorine atom, a perfluoroalkyl group having 1 to 4 carbon atoms, or a perfluoroalkoxy group having 1 to 4 carbon atoms, and particularly preferably a fluorine atom or a trifluoromethyl group. Preferred specific examples of the compound (2) include the compounds (2-1) and (2-2). [ka]

[0085] The polymer (21) may be a homopolymer of the above-mentioned fluorine-containing cyclic monoene, or a copolymer of the above-mentioned fluorine-containing cyclic monoene and another monomer copolymerizable therewith. However, the content of units derived from fluorinated cyclic monoenes in the total units in the polymer (21) is preferably at least 20 mol %, more preferably at least 40 mol %, and even more preferably 100 mol %.

[0086] Examples of other monomers copolymerizable with the fluorine-containing cyclic monoenes include fluorine-containing dienes, monomers having a reactive functional group in the side chain, tetrafluoroethylene, chlorotrifluoroethylene, perfluoroalkyl vinyl ethers, and the like. Examples of the fluorine-containing diene include those mentioned in the description of the polymer (22) described later. Examples of the monomer having a reactive functional group in the side chain include a monomer having a polymerizable double bond and a reactive functional group. Examples of the polymerizable double bond include CF2=CF-, CF2=CH-, CH2=CF-, CFH=CF-, CFH=CH-, CF2=C-, CF=CF-, etc. Examples of the reactive functional group include those mentioned in the description of the polymer (22) described later. The polymer obtained by copolymerization of a fluorinated cyclic monoene and a fluorinated diene is referred to as polymer (21).

[0087] Polymer (22): The "fluorine-containing diene" is a fluorine-containing monomer having two polymerizable double bonds and a fluorine atom, which can undergo cyclic polymerization. As the polymerizable double bond, a vinyl group, an allyl group, an acryloyl group, or a methacryloyl group is preferable. As the fluorine-containing diene, the following compound (3) is preferable. CF2=CF-Q-CF=CF2 (3)

[0088] In formula (3), Q is a perfluoroalkylene group having 1 to 5 carbon atoms, preferably 1 to 3 carbon atoms, which may contain an ether oxygen atom and may have a branch, in which some of the fluorine atoms may be substituted with halogen atoms other than fluorine atoms. Examples of the halogen atoms other than fluorine atoms include chlorine atoms and bromine atoms. Q is preferably a perfluoroalkylene group containing an etheric oxygen atom.In this case, the etheric oxygen atom in the perfluoroalkylene group may be present at one end of the perfluoroalkylene group, may be present at both ends of the perfluoroalkylene group, or may be present between the carbon atoms of the perfluoroalkylene group.From the viewpoint of cyclic polymerization, it is preferable that an etheric oxygen atom is present at one end of the perfluoroalkylene group.

[0089] Specific examples of compound (3) include the following compounds. CF2=CFFOCF2CF=CF2, CF2 = CFOCF(CF3)CF = CF2, CF2=CFFOCF2CF2CF=CF2, CF2 = CFOCF2CF(CF3)CF = CF2, CF2 = CFOCF(CF3)CF2CF = CF2, CF2=CFOCFClCF2CF=CF2, CF2=CFOCCl2CF2CF=CF2, CF2 = CFOCF2OCF = CF2, CF2 = CFOC(CF3)2OCF = CF2, CF2 = CFOCF2CF(OCF3)CF = CF2, CF2=CFCF2CF=CF2, CF2=CFCF2CF2CF=CF2, CF2=CFCF2OCF2CF=CF2.

[0090] Examples of units formed by cyclopolymerization of compound (3) include the following units (3-1) to (3-4). [ka]

[0091] The polymer (22) may be a homopolymer of a fluorinated diene, or a copolymer of a fluorinated diene and another monomer copolymerizable therewith. Examples of other monomers copolymerizable with the fluorine-containing diene include monomers having a reactive functional group in the side chain, tetrafluoroethylene, chlorotrifluoroethylene, perfluoro(methyl vinyl ether), and the like.

[0092] A specific example of the polymer (22) is a polymer having a unit represented by the following formula (3-1-1), which is obtained by cyclopolymerization of CF2=CFOCF2CF2CF=CF2 (perfluoro(3-butenyl vinyl ether)). In the following, perfluoro(3-butenyl vinyl ether) will be referred to as "BVE." [ka] In the formula (3-1-1), p is an integer of 5 to 1,000. p is preferably an integer of 10 to 800, and particularly preferably an integer of 10 to 500.

[0093] As the polymer (2), a synthesized product or a commercially available product may be used. Specific examples of the polymer (2) that may be preferred include BVE cyclized polymer (manufactured by AGC: Cytop (registered trademark)), tetrafluoroethylene / perfluoro(4-methoxy-1,3-dioxole) copolymer (manufactured by Solvay: Hyflon (registered trademark) AD), tetrafluoroethylene / perfluoro(2,2-dimethyl-1,3-dioxole) copolymer (manufactured by Dupont: Teflon (registered trademark) AF), and perfluoro(4-methyl-2-methylene-1,3-dioxolane) polymer (MMD polymer).

[0094] (Terminal Structure of Fluorine-Containing Polymer) The fluorine-containing polymer is usually polymerized by radical polymerization of each of the above-mentioned monomers using a radical polymerization initiator. In this case, the fluorine-containing polymer at the end of the polymerization is considered to have a structure at the end of the molecular chain (main chain) to which a fragment of the radical polymerization initiator used in the polymerization is added. In addition, when a chain transfer agent is used in the polymerization, the structure at the end of the molecular chain (main chain) may have a structure to which a fragment of the chain transfer agent is added. The above-mentioned terminal structure of the fluoropolymer may be converted to another structure. For example, by heat-treating the above-mentioned fluoropolymer at the end of the polymerization at 250° C. or more, the terminal structure of the main chain becomes —C(═O)—F, and the fluoropolymer becomes an acid fluoride.

[0095] By treating the acid fluoride with methanol, the structure of the terminal of the main chain becomes a methyl ester group. The methyl ester group can be converted from the highly reactive acid fluoride by a simple methanol treatment. Therefore, it is preferable because the stability of the obtained fluorine-containing polymer can be easily improved. Furthermore, by subjecting the acid fluoride to fluorination treatment, the structure of the end of the main chain becomes a trifluoromethyl group. For example, the fluorination treatment can be the treatment method described in paragraph 0040 of JP-A-11-152310. The trifluoromethyl group is preferable because it has high heat resistance and the heat resistance of the obtained fluorine-containing polymer is easily improved. In addition, when the end is a trifluoromethyl group, the surface energy of the obtained resin film is low, and it is difficult to form a metal film on the surface of the film made of the fluorine-containing polymer, and it is easy to pattern it, so it is preferable. Furthermore, it is preferable that the fluorine-containing polymer has a terminal structure of a main chain of a methyl ester group or a trifluoromethyl group, since the intermolecular interaction at the terminal of the main chain is small and deposition is facilitated. The above-mentioned structure of the main chain terminal can be confirmed by infrared spectroscopy.

[0096] (Molecular Weight of Fluorine-Containing Polymer) Highly crystalline fluorine-containing polymers have low solubility in solvents, making it difficult to measure the molecular weight. However, amorphous fluorine-containing polymers have high solubility in fluorine-containing solvents, making it possible to measure the molecular weight by gel permeation chromatography (GPC) or other methods.

[0097] The weight average molecular weight (hereinafter referred to as "Mw") of the fluorine-containing polymer is preferably from 1,000 to 20,000, more preferably from 1,500 to 15,000, and even more preferably from 2,000 to 10,000.

[0098] If the weight average molecular weight is less than 1000, the softening temperature of the fluororesin will be low, and the shape of the film made of the fluoropolymer may not be maintained at the process temperature in the device fabrication or under the conditions of use of the device. If the weight average molecular weight is more than 20,000, the main chain of the fluorine-containing polymer is cleaved during deposition, the molecular weight of the fluorine-containing polymer is reduced, the strength of the layer formed is insufficient, and defects due to decomposition products are generated, making it difficult to obtain a smooth surface. In addition, it is assumed that molecules or ions unintentionally mixed in due to the cleavage of the main chain may affect the conductivity of the conductive film adjacent to the resin film made of the fluorine-containing polymer. In addition, when a resin film is produced using the fluorine-containing polymer of this embodiment and the obtained resin film is used to pattern the conductive film as described below, the life of the element having the conductive film (for example, the light emission life of an organic EL element) may be shortened. Therefore, when the Mw of the fluoropolymer is in the range of 1,000 to 20,000, the main chain of the fluoropolymer will not be cleaved, and a layer having sufficient strength and a smooth surface can be formed.

[0099] The weight average molecular weight of the fluoropolymer is a value measured using gel permeation chromatography (GPC). First, a PMMA standard sample with a known molecular weight is measured using GPC, and a calibration curve is created from the peak top elution time and molecular weight. Next, the fluoropolymer is measured, and Mw and Mn are obtained from the calibration curve. A mixed solvent of 1,1,1,2,3,4,4,5,5,5-decafluoro-3-methoxy-2-(trifluoromethyl)pentane / hexafluoroisopropyl alcohol (volume ratio 85 / 15) is used as the mobile phase solvent.

[0100] "Molecular weight distribution" refers to the ratio of Mw to the number average molecular weight (hereinafter referred to as "Mn"), i.e., Mw / Mn. From the viewpoint of the stability of the quality of the layer to be formed, the molecular weight distribution (Mw / Mn) of the fluoropolymer is preferably small, and is preferably 2 or less. The molecular weight distribution of the fluoropolymer is more preferably 1.5 or less, and further preferably 1.2 or less. The theoretical lower limit of the molecular weight distribution is 1. The narrower the molecular weight distribution of the fluorine-containing polymer, the less the fluctuation in deposition conditions becomes, and the more easily a homogeneous phase-separated structure is formed in the film thickness direction.

[0101] Methods for obtaining a fluorine-containing polymer having a narrow molecular weight distribution include molecular weight adjustment by controlled polymerization such as living radical polymerization, and molecular weight fractionation by sublimation purification, supercritical extraction, and size exclusion chromatography. In this specification, the weight average molecular weight and molecular weight distribution are values ​​measured by gel permeation chromatography (GPC).

[0102] (Surface energy of resin film) The above-mentioned fluoropolymer is preferably one having a surface energy of 30 mN / m or less, more preferably 25 mN / m or less, and even more preferably 20 mN / m or less, of a resin film made of the fluoropolymer as a material. If the resin film has such a surface energy, when a metal material is dry-coated, the metal material is less likely to adhere to the surface of the resin film, making patterning easier. The surface energy of the resin film can be adjusted by changing the fluorine atom content or the trifluoromethyl moiety content of the fluorine-containing polymer used. Increasing the fluorine atom content or the trifluoromethyl moiety content of the fluorine-containing polymer reduces the surface energy of the resin film.

[0103] (Resin film) 2 and 3 are explanatory diagrams showing the resin film of this embodiment, and more specifically, explanatory diagrams of a conductive film manufactured using the resin film. Fig. 2 is a plan view of a conductive film 1 having a resin film, and Fig. 3 is a cross-sectional view taken along line III-III in Fig. 2.

[0104] As shown in FIGS. 2 and 3, the conductive film 1 has a first film 10, a resin film 15 of this embodiment, and a second film 20. The conductive film 1 is provided on a substrate 50. The substrate 50 is an object on which the conductive film 1 is formed. The substrate 50 has optical transparency. The second film 20 is provided on the substrate 50, and the first film 10 is provided on the second film 20. The resin film 15 is provided between the first film 10 and the second film 20. That is, the first film 10, the resin film 15, and the second film 20 are laminated in this order on the substrate 50.

[0105] (1st membrane) The first film 10 is a metal film made of a first conductive material. Examples of the first conductive material that is the material of the first film 10 include metals such as silver (Ag), gold (Au), copper (Cu), aluminum (Al), magnesium (Mg), magnesium silver (MgAg), and ytterbium silver (YbAg), and conductive oxides such as indium tin oxide (ITO), indium zinc oxide (IZO), and zinc oxide (ZnO).

[0106] The first film 10 has a first region 10A and a second region 10B having a higher light transmittance than the first region 10A. In the conductive film 1, a conductive film 11 is located in the first region 10A, and a conductive film 12 is located in the second region 10B. The conductive films 11 and 12 are integrated to form the first film 10. 2, in the conductive film 1, a plurality of second regions 10B, i.e. a plurality of conductive films 12, are arranged in a matrix, and the remaining portion has a lattice-shaped first region 10A, i.e., a lattice-shaped conductive film 11. In FIG. 2, the second region 10B is rectangular in plan view, but is not limited thereto and various plan view shapes can be adopted according to the design.

[0107] The lower surface 11a of the conductive film 11 is in contact with the second film 20. In addition, the side surface 11b of the conductive film 11 is in contact with the resin film 15. The lower surface 12 a of the conductive film 12 is in contact with the resin film 15 . The conductive film 12 is thinner than the conductive film 11. For example, the thickness of the conductive film 11 is 10 nm to 1000 nm, and the thickness of the conductive film 12 is 0 nm to 50 nm. The conductive film 11 formed to a thickness of 50 nm or less has optical transparency. The conductive film 11 is formed thicker than the conductive film 12 in order to ensure the conductivity of the entire conductive film 1. The conductive film 11 may or may not be optically transparent as long as it can ensure the required conductivity.

[0108] (Second membrane) The second film 20 is provided on the surface 50a of the substrate 50. The second film 20 is a metal film made of a second conductive material. Examples of the second conductive material that is the material of the second film 20 include the same materials that can be used as the first conductive material. The first conductive material, which is the material of the first film 10, and the second conductive material, which is the material of the second film 20, may be the same or different. In order to suppress the contact resistance at the interface between the first film 10 and the second film 20, it is more preferable that the first conductive material and the second conductive material are the same.

[0109] The second film 20 is optically transparent. The second film 20 has a higher optical transmittance than the conductive film 11. The thickness of the second film 20 is 5 nm to 60 nm. Moreover, the second film 20 overlaps with the conductive film 12 in plan view. Therefore, the film thickness of the second film 20 and the total film thickness of the conductive film 12 may be appropriately adjusted so that the second region 10B has optical transparency.

[0110] It is also possible to use only the second film 20 as a transparent electrode used in various optoelectronic elements such as a light emitting element, a light receiving element, etc. On the other hand, the second film 20 formed thin enough to have optical transparency has high wiring resistance. In contrast, the conductive film 1 is formed by laminating a second film 20 and a first film 10. Therefore, in the position overlapping with the first region 10A, the conductive film 11 and the second film 20 are laminated to form a thick film. This allows the resistance of the conductive film 1 as a whole to be reduced while ensuring light transparency in the position overlapping with the second region 10B.

[0111] (Resin film) The resin film 15 is made of the fluoropolymer of the present embodiment described above. The resin film 15 is disposed so as to overlap the second region 10B. The resin film 15 is used to pattern the first region 10A and the second region 10B of the first film 10 by dry coating, as will be described in the conductive film manufacturing method described later. The fluoropolymer, which is the material of the resin film 15, has low absorbance and a low refractive index, and therefore has the advantage of having little light absorption and excellent optical properties over a wide wavelength range including the near-infrared region. Therefore, even if the resin film 15 overlaps with the second region 10B, which has optical transparency, the resin film 15 does not inhibit the optical transparency of the second region 10B.

[0112] The above-mentioned fluoropolymer of this embodiment has physical properties suitable for the production method described below, and therefore, by using the fluoropolymer of this embodiment, a suitably patterned conductive film 1 can be produced.

[0113] (Method of manufacturing conductive film) 4 to 6 are schematic diagrams showing a method for producing the above-mentioned conductive film 1. As described below, by using a resin film made of the above-mentioned fluorine-containing polymer, a conductive film 1 having desired physical properties can be easily produced. First, as shown in Fig. 4, the above-mentioned second conductive material is formed on the surface of the substrate 50 to obtain the second film 20. The second film 20 can be formed by a dry coating method such as deposition, sputtering, CVD (chemical vapor deposition), or ALD (Atomic Layer Deposition). The second film 20 corresponds to the "underlayer" of the present invention.

[0114] 5, the fluoropolymer P of this embodiment is deposited under reduced pressure on the surface 20a of the second film 20 through a mask M. The mask M has openings M2 arranged in a matrix and shielding portions M1 arranged in a lattice pattern. The deposition of the fluorine-containing polymer P is, for example, 1×10 -3 The reaction is carried out by heating the fluoropolymer under a pressure of 100 Pa.

[0115] The fluoropolymer P passes through the openings M2 of the mask M to reach the surface 20a of the second film 20, but is blocked by the blocking portions M1 of the mask M. In this way, a resin film 15 made of the fluoropolymer P is formed. The resin film 15 is arranged in a matrix on the surface 20a. In addition, in the areas where the resin film 15 is not formed, the second film 20 is exposed in a lattice pattern.

[0116] 6, the above-mentioned first conductive material 10X is dry-coated from above the resin film 15. As the dry coating, vapor deposition, sputtering, ALD (Atomic Layer Deposition), or the like can be used.

[0117] The first conductive material 10X does not easily adhere to the surface of the resin film 15 made of a fluorine-containing polymer, but easily adheres to the surface of the second film 20 made of the second conductive material. Therefore, by dry-coating the first conductive material 10X over the entire surface of the substrate 50 from above without using a mask, the first conductive material 10X is formed in a relatively thick film on the surface of the second film 20, and the first conductive material 10X is formed in a relatively thin film on the surface of the resin film 15. In other words, by dry-coating the first conductive material 10X over the entire surface of the substrate 50 from above, the first conductive material 10X is patterned into a portion where the resin film 15 is provided and a portion where the resin film 15 is not provided. As a result, a lattice-shaped conductive film 11 is formed on the surface of the second film 20. Furthermore, a matrix-shaped conductive film 12 is formed corresponding to the positions of the resin films 15. The conductive films 11 and 12 constitute the first film 10.

[0118] This results in the conductive film 1. The location where the conductive film 11 is formed is the first region 10A. Moreover, the location where the conductive film 12 is formed is the second region 10B. If one were to directly manufacture the conductive film 11 by mask vapor deposition, it would be necessary to use a mask having shielding portions in a matrix. Such a mask requires a holding portion for holding the shielding portions, and therefore the conductive film 11 is not formed in the portions blocked by the holding portion, and the thickness of the resulting conductive film 11 is likely to vary. Alternatively, it is possible to form a lattice-shaped conductive film 11 by vapor deposition in multiple steps using a striped mask, but this makes it difficult to align the mask and the work complicated. Furthermore, when the mask material is a metal, if the conductive film 11 is to be manufactured by vapor deposition, the first conductive material 10X to be vapor deposited may gradually adhere to the metal mask, causing a change in the size of the opening in the mask. In this case, it is necessary to either wash off the first conductive material 10X adhering to the metal mask or replace it with a new mask, which requires complicated work and huge costs.

[0119] On the other hand, in the above-mentioned manufacturing method, as shown in Fig. 6, a resin film 15 made of the above-mentioned fluorine-containing polymer P is formed, and then a first conductive material 10X is deposited on the entire surface, thereby naturally obtaining a first film 10 in which a conductive film 11 and a conductive film 12 are patterned. The resin film 15 can be precisely formed by mask deposition. Therefore, according to the above-mentioned manufacturing method of a conductive film, a precisely patterned conductive film can be easily manufactured.

[0120] The fluoropolymer having the above-mentioned structure is suitable for vapor deposition and can be suitably patterned into metal. The resin film having the above-mentioned structure enables suitable metal patterning.

[0121] [Second embodiment] 7 is a cross-sectional view showing an optoelectronic device (organic EL device) 100 according to a second embodiment of the present invention. The organic EL device 100 has a laminated structure of a substrate 110, an anode 111, a partition wall 112, a functional layer 113, and a cathode 115. The functional layer 113 includes a light-emitting layer. The organic EL element 100 of this embodiment employs a top emission system in which light generated in the functional layer 113 is emitted to the outside via the cathode 115.

[0122] (substrate) The substrate 110 may or may not have optical transparency. The substrate 110 may be made of inorganic materials such as glass, quartz glass, silicon nitride, etc., or organic polymers (resins) such as polyimide resin, acrylic resin, polycarbonate resin, etc. Furthermore, as long as the insulating properties of the surface are ensured, a metal material may also be used as the substrate 110. The substrate 110 also includes various wirings and driving elements (not shown) that are electrically connected to the organic EL elements.

[0123] (anode) The anode 111 is formed on the substrate 110, and supplies holes to the functional layer 113. In addition, the anode 111 has light reflectivity that reflects light emitted from a light-emitting layer included in the functional layer 113. The anode 111 can be made of a conductive metal oxide such as ITO (Indium Tin Oxide) or IZO (Indium Zinc Oxide). In order to impart light reflectivity to the anode 111, a reflective film made of a metal material is provided on the substrate 110 side of the anode 111 or on the functional layer 113 side of the anode 111. In other words, the anode 111 has a laminated structure of a layer made of a conductive metal oxide and a reflective film. The anode 111 may be made of silver. The thickness of the anode 111 is not particularly limited, but is preferably 30 to 300 nm, and is, for example, 100 nm.

[0124] (bulkhead) The partitions 112 are formed, for example, in a lattice shape, and overlap the periphery of the anode 111. In the openings of the partitions 112, functional layers 113 are formed to separate the organic EL elements 100. The partition wall 112 is made of, for example, polyimide.

[0125] (Functional layer) The functional layer 113 is formed to overlap the anode 111. The functional layer 113 has a light-emitting layer. In the light-emitting layer, holes injected from the anode 111 and electrons injected from the cathode 115 recombine to emit photons and emit light. The emission wavelength at that time is determined by the material from which the light-emitting layer is formed. The light-emitting layer corresponds to the "active layer" in the present invention.

[0126] The light-emitting layer can be formed using a material known as a material for the light-emitting layer of an organic EL element. The materials for forming the light-emitting layer may be used alone or in combination of two or more kinds, and are appropriately selected according to the desired emission wavelength.

[0127] The functional layer 113 may have a hole injection layer and a hole transport layer between the light emitting layer and the anode 111 . The hole injection layer has the function of facilitating the injection of holes from the anode to the hole transport layer. The hole transport layer has a function of efficiently transporting holes injected from the anode 111 toward the light emitting layer. Furthermore, the functional layer 113 may have an electron transport layer and an electron injection layer between the light emitting layer and the cathode 115 . The electron transport layer has a function of efficiently transporting electrons injected from the cathode 115 toward the light emitting layer. The electron injection layer has the function of facilitating the injection of electrons from the cathode 115 to the electron transport layer.

[0128] (cathode) The cathode 115 is formed on the entire surface so as to cover the partition wall 112 and the functional layer 113. The cathode 115 has a function of injecting electrons into the functional layer. In the optoelectronic device of this embodiment, the cathode 115 includes the resin film of the present invention described above and is patterned. The cathode 115 has a first film 116, a resin film 117, and a second film 118.

[0129] The second film 118 is formed to cover the partition walls 112 and the functional layer 113. The configuration and material of the second film 118 may be the same as those shown for the second film 20 of the first embodiment. The resin film 117 overlaps the functional layer 113 in plan view and is formed on the upper surface 118a of the second film 118. As for the configuration and material of the resin film 117, the fluorine-containing polymer according to this embodiment can be used, like the resin film 15 of the first embodiment.

[0130] The first film 116 is formed to overlap with the partition wall 112 in a plan view. The configuration and material of the first film 116 may be the same as those shown for the first film 10 of the first embodiment. That is, a first region of the cathode 115 overlaps with the partition wall 112, and a second region of the cathode 115 overlaps with the functional layer 113 including the light-emitting layer.

[0131] (Microcavity structure) In the organic EL element 100 of this embodiment, the anode 111 and the cathode 115 form an optical resonance structure (microcavity) that resonates light between the anode 111 and the cathode 115, i.e., between the upper surface of the reflective film of the anode 111 and the lower surface of the second film 118. Between the anode 111 and the cathode 115, light generated in the light-emitting layer is repeatedly reflected, and light with a wavelength that matches the optical path length between the anode 111 and the cathode 115 resonates and is amplified. On the other hand, light with a wavelength that does not match the optical path length between the anode 111 and the cathode 115 is attenuated. The "optical path length" here is calculated using the wavelength of the desired light emitted outside the element and the refractive index of each layer at the wavelength of the desired light.

[0132] The optical path length between the anode 111 and the cathode 115 is set to, for example, an integer multiple of the central wavelength of the light L generated in the light-emitting layer included in the functional layer 113. In this case, the light L emitted from the light-emitting layer is amplified as it approaches the central wavelength and is attenuated as it departs from the central wavelength, before being emitted to the outside of the organic EL element 100. In this way, the light L emitted from the organic EL element 100 has a narrow half-width of the emission spectrum and improved color purity.

[0133] In the organic EL element 100 having such a configuration, since the resin film 117 is a resin layer made of the fluorine-containing polymer of the present invention, the metal (first film 116) can be suitably patterned in the second region. Therefore, the wiring resistance of the cathode 115 can be reduced while maintaining high light extraction efficiency in the second region, and good driving can be achieved.

[0134] In the above embodiment, an organic EL element has been described as an example of an optoelectronic element. However, the optoelectronic element to which the resin film according to an aspect of the present invention is applied is not limited to an organic EL element.

[0135] The optoelectronic device according to one aspect of the present invention may be, for example, a semiconductor laser. A known configuration can be adopted for the semiconductor laser. By patterning a conductive film using the above-mentioned resin film on the cathode of the semiconductor laser, the resistance of the cathode is reduced, resulting in a semiconductor laser with improved output.

[0136] Furthermore, the optoelectronic device according to one aspect of the present invention may be, for example, a light receiving element such as a photosensor, a solar cell, etc. As the photosensor and the solar cell, a known configuration can be adopted in which holes and electrons generated in an active layer (light receiving layer) according to the intensity of light received by the active layer are transferred to a cathode and an anode via a semiconductor layer. By patterning a conductive film using the above-mentioned resin film on the electrodes (anode, cathode) of a photosensor and a solar cell, a photosensor with improved detection performance and an organic solar cell with improved power generation efficiency can be obtained.

[0137] Furthermore, in the optoelectronic device according to one embodiment of the present invention, the use of the above-mentioned resin film allows suitable patterning of the metal film, and the transmittance of the entire device is increased, making it useful in applications such as transparent displays, etc. In under-display cameras, under-display sensors, etc., it is necessary to increase the transmittance of the display above the camera and sensor, and patterning using the resin film of the present invention is very useful. That is, the fluorine-containing polymer of the present invention has excellent light transmittance and can therefore be suitably applied to the above-mentioned optoelectronic device.

[0138] Furthermore, the resin film of the present invention can also be used in forming patterned electrodes and wiring other than optoelectronic elements.

[0139] Although the preferred embodiment of the present invention has been described above with reference to the accompanying drawings, the present invention is not limited to the above embodiment. The shapes and combinations of the components shown in the above embodiment are merely examples, and various modifications can be made based on design requirements, etc., without departing from the spirit of the present invention. EXAMPLES

[0140] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.

[0141] <Evaluation method> In this embodiment, evaluation was performed by the following methods.

[0142] [Measurement of thermal weight loss rate of fluoropolymer under vacuum] The measurement was performed using a vacuum differential thermobalance (Advance Riko Co., Ltd.: VPE-9000). 50 mg of fluoropolymer was placed in a cell with an inner diameter of 7 mm, and the temperature was measured at 1 × 10 -3 The weight loss rate (%) of the fluoropolymer relative to the initial weight (50 mg) was measured when the temperature was raised from room temperature to 500° C. at a rate of 2° C. per minute under a vacuum of 100 Pa.

[0143] The temperature at which the weight loss rate reaches 100% (T d100 ), the temperature at which the weight loss rate becomes 10% (T d10 ) and the temperature at which the weight loss rate reaches 90% (T d90 ) was sought.

[0144] [Melt point measurement] Measurement was performed using a differential scanning calorimeter (NETZSCH: DSC 204 F1 Phoenix). 9 mg of the fluoropolymer was placed in a sample container, and the heat capacity was measured while the temperature was raised from -70°C to 350°C at 10°C per minute, and the melting point was calculated from the obtained melting peak.

[0145] (Measurement of CF3 concentration) The content (mmol / g) of trifluoromethyl moieties was calculated from the following formula. (Fluoromethyl moiety content) = [NCF3 / MA] x 1000 NCF3: the sum of values ​​obtained by multiplying the number of moles of trifluoromethyl moieties constituting the units by the molar ratio of the units to all units for each type of unit constituting the fluorinated polymer. MA: the sum of the values ​​obtained by multiplying the total atomic weight of all atoms constituting the unit by the molar ratio of the unit to all units for each type of unit constituting the fluorine-containing polymer. The number of moles of the trifluoromethyl moiety, the total atomic weights of all atoms constituting the unit, the molar ratio, etc. used in the above formula were calculated using the molar ratios and terminal amounts of the constituent units of the fluorine-containing polymer obtained by NMR analysis and IR analysis of the fluorine-containing polymer.

[0146] (Measurement of fluorine atom content) The fluorine atom content (mass %) was calculated by the following formula. (Fluorine atom content) = [19 x NF / MA] x 100 NF: the sum of the values ​​obtained by multiplying the total atomic weight of fluorine atoms constituting each type of unit constituting a fluorine-containing polymer by the molar ratio of that unit to all units. MA: the sum of the values ​​obtained by multiplying the total atomic weight of all atoms constituting the unit by the molar ratio of the unit to all units for each type of unit constituting the fluorine-containing polymer. The atomic weight of the fluorine atom, the total atomic weight of all atoms constituting the unit, the molar ratio, etc. used in the above formula were calculated using the molar ratio and terminal amount of the constituent units of the fluorine-containing polymer obtained by NMR analysis and IR analysis of the fluorine-containing polymer.

[0147] <Synthesis of Fluorine-Containing Polymer> The fluorine-containing polymers used for the evaluation were synthesized as follows.

[0148] [Synthesis Example 1] A stainless steel autoclave with an internal volume of 1006 mL was charged with 152.9 g of PPVE, 805 g of AC2000 (AGC), 2.40 g of methanol, and 1.15 g of azobisisobutyronitrile (AIBN), and the contents were frozen and degassed with liquid nitrogen. After the temperature of the autoclave was raised to 70°C, 56.3 g of TFE was introduced into the autoclave to initiate polymerization. As the polymerization proceeded, the pressure inside the autoclave decreased, so TFE was continuously fed and polymerization was continued while maintaining the temperature and pressure of the autoclave constant. Five hours after the start of polymerization, the autoclave was cooled to terminate the polymerization, and the gas in the system was discharged to obtain a reaction solution.

[0149] The reaction solution was mixed with 800 g of methanol to precipitate the polymer dissolved in the reaction solution, and then the layers were separated and the lower layer in which the polymer was dispersed was collected. The resulting polymer dispersion was dried with hot air at 80°C for 16 hours, and then vacuum dried at 100°C for 16 hours to obtain a polymer. The composition of the obtained polymer was PPVE units:TFE units=14:86 (mol %).

[0150] The obtained polymer was then heated in an oven at 330° C., immersed in methanol and heated in an oven at 75° C. for 40 hours to substitute the terminal groups with methyl ester groups, thereby obtaining a fluorine-containing polymer C.

[0151] The obtained fluoropolymer C was charged into the raw material charging section of the above-mentioned glass tube type sublimation purification apparatus, and the inside of the collection section was filled with 3.0×10 -3 The pressure was reduced to 100 Pa. Then, the raw material supply section was gradually heated to 330°C to sublimate the fluoropolymer C. In the sublimation purification apparatus, the collection section was heated at set temperatures of 310°C, 280°C, 250°C, and 200°C from the side closer to the supply section. Of this, the substance precipitated in the collection section set at a temperature of 280° C. was recovered to obtain 2 g of a purified fluoropolymer C1.

[0152] [Synthesis Example 2] A jacketed polymerization tank (made of stainless steel) with an internal volume of 1.351 L was degassed, and 433 g of AE-3000 (manufactured by AGC), 360 g of PPVE, 120 g of TFE, and 15 g of methanol were weighed and charged into the polymerization tank. The temperature was maintained at 60°C, and 15 mL of a 3.33 mass% solution of t-butyl peroxypivalate (PBPV) (solvent: AE-3000) was charged to initiate polymerization. During polymerization, TFE was introduced into the polymerization tank, and the polymerization pressure was maintained at 1.00 MPa in gauge pressure. Since the polymerization pressure decreased with the progress of the polymerization, TFE was continuously charged so that the polymerization pressure was kept almost constant. When the amount of TFE introduced reached 121 g, the polymerization was terminated to obtain a fluorine-containing copolymer.

[0153] The resulting polymer was then heated in an oven at 300° C., immersed in methanol, and heated in an oven at 75° C. for 40 hours to replace the terminal groups with methyl ester groups, thereby obtaining a fluorinated polymer X. The composition of the obtained fluoropolymer X was PPVE units:TFE units=12:88 (mol %).

[0154] The fluoropolymer X was sublimated in the same manner as in Synthesis Example 1. The collection section was heated from the side closer to the feed section at set temperatures of 310°C, 280°C, 220°C, and 160°C, and the substances precipitated in the collection sections at set temperatures of 220°C and 280°C were recovered to obtain 2 g of purified fluoropolymer X1.

[0155] [Synthesis Example 3] A polymer was obtained in the same manner as in Synthesis Example 1, except that 78.9 g of PPVE, 767 g of AC2000, 4.23 g of methanol, 1.27 g of AIBN, and 48.4 g of TFE were used. The composition of the obtained polymer was PPVE units:TFE units=9:91 (mol %).

[0156] Then, in the same manner as in Synthesis Example 1, the terminal groups of the polymer were substituted with methyl ester groups to obtain a fluorine-containing polymer D. Fluorine-containing polymer D was sublimated in the same manner as in Synthesis Example 1. The substances precipitated in the collection sections set at temperatures of 250° C. and 280° C. were recovered to obtain 4 g of purified fluorine-containing polymer D1.

[0157] [Synthesis Example 4] A polymer was obtained in the same manner as in Synthesis Example 1, except that 57.9 g of PPVE, 4.13 g of methanol, and 1.24 g of AIBN were used. The composition of the obtained polymer was PPVE units:TFE units=6:94 (mol %).

[0158] Then, the terminal groups of the polymer were substituted with methyl ester groups in the same manner as in Synthesis Example 1 to obtain a fluorine-containing polymer E. Fluorine-containing polymer E was sublimated in the same manner as in Synthesis Example 1. Substances precipitated in collection sections set at temperatures of 200° C., 250° C. and 280° C. were recovered to obtain 5 g of purified fluorine-containing polymer E1.

[0159] [Synthesis Example 5] A jacketed polymerization tank (made of stainless steel) having an internal volume of 1.351 L was degassed, and 649 g of AE-3000, 152 g of PPVE, 109 g of TFE, and 15.5 g of methanol were weighed and charged into the polymerization tank. The temperature of the polymerization tank was maintained at 60° C., and 18.9 mL of a 0.79 mass % solution of t-butyl peroxypivalate (PBPV) (solvent: AE-3000) was charged to initiate polymerization.

[0160] During the polymerization, the polymerization pressure decreased with the progress of the polymerization, so TFE was continuously introduced into the polymerization tank so that the polymerization pressure was kept almost constant. The polymerization pressure was maintained at 1.04±0.04 MPaG (gauge pressure).

[0161] When the amount of TFE introduced reached 121 g, the polymerization was terminated to obtain a polymer. The composition of the obtained polymer was PPVE units:TFE units=4:96 (mol %).

[0162] Next, the terminal groups of the obtained polymer were substituted with methyl ester groups under the same conditions as in Synthesis Example 1 to obtain a fluoropolymer G. Fluoropolymer G was sublimated in the same manner as in Synthesis Example 1. The substance precipitated in a collector set at a temperature of 250° C. was recovered to obtain 4 g of purified fluoropolymer G1.

[0163] [Synthesis Example 6] A polymer was obtained in the same manner as in Synthesis Example 5, except that 701 g of AE-3000, 57 g of PPVE, 108 g of TFE, 35.7 g of methanol, and 18.9 mL of a 0.53 mass % solution of PBPV (solvent: AE-3000) were used.

[0164] The composition of the obtained fluoropolymer was PPVE units:TFE units=2:98 (mol %).

[0165] Next, the terminal groups of the obtained polymer were substituted with methyl ester groups under the same conditions as in Synthesis Example 1, to obtain a fluoropolymer I. Fluorine-containing polymer I was sublimated in the same manner as in Synthesis Example 1. Substances precipitated in collection sections set at temperatures of 250° C. and 280° C. were recovered to obtain 4 g of purified fluorine-containing polymer I1.

[0166] [Synthesis Example 7] A jacketed polymerization tank (made of stainless steel) with an internal volume of 1.351 L was degassed, and 331 g of R113 (1,1,2-trifluorotrichloroethane, manufactured by AGC), 1.1 g of methanol, and 765 g (5.1 mol) of HFP were charged into the polymerization tank, followed by TFE. TFE was charged so that the pressure in the polymerization tank was 0.62 MPaG at a temperature of 50°C.

[0167] Then, a 0.3% by mass solution of Perloyl FB (solvent: R113) was charged to start the polymerization. As the polymerization progressed, the polymerization pressure decreased, so TFE was continuously charged to keep the polymerization pressure almost constant. A 0.3% by mass solution of Perloyl FB (solvent: R113) was intermittently charged, and the polymerization was terminated when 71 g (0.71 mol) of TFE was consumed, to obtain a fluorine-containing copolymer. The composition of the obtained polymer was HFP units:TFE units=20:80 (mol %).

[0168] The resulting polymer was then heated in an oven at 330° C., immersed in methanol, and heated in an oven at 75° C. for 40 hours to replace the terminal groups with methyl ester groups, thereby obtaining a fluorine-containing polymer Y. Fluoropolymer Y was sublimated in the same manner as in Synthesis Example 2. Substances precipitated in collection sections set at temperatures of 160° C., 220° C., 280° C. and 310° C. were recovered to obtain 4 g of purified fluoropolymer Y1.

[0169] [Commercially available fluorine-containing polymers] As commercially available fluorine-containing polymers, the following materials were used for evaluation. Fluon PTFE L173JE (AGC): Tetrafluoroethylene polymer Fluon PFA P-63 (AGC): Tetrafluoroethylene / perfluoropropyl vinyl ether copolymer TEFLON AF 1600 (DuPont): Tetrafluoroethylene / perfluoro(2,2-dimethyl-1,3-dioxole) copolymer Kynar 301F (Arkema): vinylidene fluoride polymer Kynar 720 (Arkema): vinylidene fluoride polymer

[0170] <Evaluation> The obtained fluoropolymer was subjected to the following evaluations 1 to 4.

[0171] [Evaluation 1: Change in chamber pressure during deposition] 0.1 g of fluoropolymer was charged into the vacuum deposition apparatus, and the pressure in the chamber was increased to 10 -4 After reducing the pressure to below 1 Pa, a fluoropolymer film was formed at a deposition rate of 0.1 nm / sec to a thickness of 200 nm. The pressure in the chamber was monitored during this process, and the maximum pressure during deposition was measured. The measured value was used to calculate the pressure increase rate according to the following formula. [Chamber pressure increase rate during deposition] = [Maximum pressure during deposition] / [Initial pressure before deposition]

[0172] Fluorine-containing polymers whose chamber pressure increase rate was 2 times or less were evaluated as "good," and fluorine-containing polymers whose chamber pressure increase rate was more than 2 times were evaluated as "poor." As for the fluoropolymers that were evaluated as defective in this evaluation, the evaluation of the conductive film that follows was abandoned due to concerns about contamination of the chamber.

[0173] [Evaluation 2: Conductive film patterning evaluation 1] (Preparation of samples for transmittance measurement) A quartz substrate measuring 25 mm×25 mm×0.525 mm was used. A fluorine-containing polymer was deposited by vapor deposition using a metal mask having a rectangular opening of 21 mm×5 mm in the center of the quartz substrate when viewed from above, to prepare a quartz substrate having a resin film. The deposition of the fluoropolymer was carried out at a deposition rate of 0.1 nm / sec until the thickness reached 10 nm as measured by a film thickness meter attached to the deposition apparatus.

[0174] Next, Ag was evaporated onto the entire surface of the resin film on the quartz substrate without using a mask, to prepare a conductive film sample for measuring transmittance. The deposition of Ag was carried out at a deposition rate of 0.05 nm / sec until the thickness of the Ag film reached 15 nm as measured by a film thickness gauge attached to the deposition apparatus.

[0175] (Transmittance measurement) The transmittance of the prepared conductive film sample was measured using a spectrophotometer (Shimadzu Corporation, model number: UV-3600 Plus). From the results, it was determined that the higher the transmittance, the better the patterning property (the easier the patterning).

[0176] [Evaluation 3: Conductive film patterning evaluation 2] (Preparation of samples for measuring total light transmittance) A quartz substrate measuring 25 mm×25 mm×0.525 mm was used. A fluorine-containing polymer was deposited by vapor deposition using a metal mask having a rectangular opening of 21 mm×5 mm in the center of the quartz substrate when viewed from above, to prepare a quartz substrate having a resin film. The deposition of the fluoropolymer was carried out at a deposition rate of 0.1 nm / sec until the thickness reached 50 nm as measured by a film thickness meter attached to the deposition apparatus.

[0177] Next, Ag was evaporated onto the entire surface of the resin film on the quartz substrate without using a mask, to prepare a conductive film sample for measuring transmittance. The deposition of Ag was carried out under two deposition rates of 0.05 nm / sec and 0.2 nm / sec until the film thickness reached 70 nm as measured by a film thickness meter attached to the deposition apparatus.

[0178] (Total light transmittance measurement) For the conductive film sample for measuring the total light transmittance, the total light transmittance of the second region was measured using a haze meter (manufactured by Suga Test Instruments, model number: HZ-V3, measuring light: D65 light).

[0179] [Evaluation 4: Flexibility of fluorine-containing polymer] The flexibility of the fluoropolymer was evaluated based on the storage modulus (G') measured using a dynamic viscoelasticity measuring device (MCR502, manufactured by Anton Paar) and a heating furnace for viscoelasticity measuring device (CTD450, manufactured by Anton Paar). Specifically, using the above-mentioned measuring device, a sample (fluoropolymer) was heated above its melting point, and then cooled at 2°C / min in a constant temperature decreasing mode, and the storage modulus (G') was measured under conditions of a strain of 0.01% and a frequency of 1 Hz. From the obtained results, the flexibility of the fluoropolymer was evaluated as follows. A: Storage modulus (G') at 40°C is 4 x 10 7 Less than Pa B: Storage modulus (G') at 40°C is 4×10 7 More than Pa

[0180] [Examples 1-7] Resin films were formed using the above-mentioned fluoropolymers C1, X1, D1, E1, G1, I1 and Y1, and evaluations 1 to 4 were carried out.

[0181] [Example 8] Evaluation was carried out in the same manner as in Example 1, except that a resin film was formed using Fluon PTFE L173JE as the fluoropolymer. Since the temperature inside the chamber rose significantly during deposition in evaluation 1, no other evaluations were performed.

[0182] [Example 9] Evaluation was carried out in the same manner as in Example 1, except that a resin film was formed using Fluon PFA P-63 as the fluorine-containing polymer. Since the temperature inside the chamber rose significantly during deposition in evaluation 1, no other evaluations were performed.

[0183] [Example 10] Evaluation was carried out in the same manner as in Example 1, except that the resin film was formed using TEFLON AF 1600 as the fluoropolymer. Since the temperature inside the chamber rose significantly during deposition in evaluation 1, no other evaluations were performed.

[0184] [Example 11] Evaluation was carried out in the same manner as in Example 1, except that the resin film was formed using Kynar 301F as the fluorine-containing polymer. Since the temperature inside the chamber rose significantly during deposition in evaluation 1, no other evaluations were performed.

[0185] [Example 12] Evaluation was carried out in the same manner as in Example 1, except that a resin film was formed using Kynar 720 as the fluorine-containing polymer. Since the temperature inside the chamber rose significantly during deposition in evaluation 1, no other evaluations were performed.

[0186] Of the above Examples 1 to 12, Examples 1, 2, and 7 correspond to working examples, Examples 3 to 6 correspond to reference examples, and Examples 8 to 12 correspond to comparative examples. The evaluation results are shown in Tables 1 to 3. Table 1 summarizes the physical properties of the resin film material, Table 2 summarizes the results of Evaluations 1 and 2, and Table 3 summarizes the results of Evaluations 3 and 4. In the tables, "-" indicates that no data is available.

[0187] [Table 1]

[0188] [Table 2]

[0189] [Table 3]

[0190] As a result of the evaluation, it was found that in Examples 1 to 7, there was no increase in the pressure inside the chamber during deposition, and no depolymerization, thermal decomposition, or outgassing was observed. Moreover, Examples 1, 2, and 7, which satisfy the requirements (1) to (3), showed high transparency of 80% or more in the evaluation of 3.

[0191] Furthermore, in Evaluation 4, Examples 1 and 2 in which the PPVE content was 11 mol% or more and Example 7 in which the HFP content was 18 mol% or more had a storage modulus (G') at 40°C of 4 × 10 7 It was confirmed that the compressive strength was less than 100 Pa and that the flexibility was high.

[0192] In contrast, in Examples 8 to 12, an increase in the pressure inside the chamber during deposition was observed, and it was found that depolymerization, thermal decomposition, and outgassing occurred during deposition, making these methods essentially unsuitable for producing the resin film of this embodiment. Moreover, Example 3 (Reference Example), which does not satisfy requirement (1), did not show a clear difference from Examples 1, 2, and 7 in Evaluation 2, but its physical properties were clearly inferior to Examples 1, 2, and 7 in Evaluation 3. Examples 4 to 6, which do not satisfy requirement (1), are also expected to have physical properties similar to those of Example 4.

[0193] From the above results, it was confirmed that the present invention is useful. [Industrial Applicability]

[0194] The present invention is a fluorine-containing polymer that can be deposited without pyrolysis or outgassing, and can be used as a metal patterning material for electrodes, etc., as well as a material for optical thin films such as OCA (Optical Clear Adhesive) for displays, OCR (Optical Clear Resin), and light extraction films. Thin films made of the fluorine-containing polymer of the present invention can be used as optical thin films with a low refractive index. In addition, the entire contents of the specifications, claims, abstracts and drawings of Japanese Patent Application No. 2020-030460 filed on February 26, 2020, Japanese Patent Application No. 2020-112962 filed on June 30, 2020, and Japanese Patent Application No. 2021-006634 filed on January 19, 2021 are hereby incorporated by reference as the disclosure of the specification of the present invention. [Explanation of symbols]

[0195] Reference Signs List 1, 11, 12...conductive film, 10, 116...first film, 10A...first region, 10B...second region, 10X...first conductive material, 15, 117...resin film, 20, 118...second film, 20a, 50a...surface, 50...base material, 110...substrate, 111...anode, 115...cathode, P...fluorine-containing polymer, M...mask

Claims

1. A fluorine-containing polymer having units derived from a fluoroolefin and satisfying the following (1) to (3): (1) The melting point is less than 200° C., or no melting point is observed. (2) 1 x 10 -3 The thermal weight loss rate when the temperature is increased at a rate of 2° C. / min under a pressure of 100 Pa reaches substantially 100% at 400° C. or less. (3) 1 x 10 -3 When the temperature is increased at a rate of 2°C / min under a pressure of 10 Pa, the temperature range from the temperature at which the thermal weight loss rate becomes 10% to the temperature at which it becomes 90% is within 200°C.

2. Storage modulus at 40°C is 4 x 10 7 The fluoropolymer according to claim 1, having a viscosity of less than Pa.

3. The fluorine-containing polymer according to claim 1 or 2, which has at least a unit derived from tetrafluoroethylene.

4. The fluorine-containing polymer according to any one of claims 1 to 3, which has a unit derived from a perfluoroalkyl vinyl ether.

5. The fluorine-containing polymer according to claim 4, wherein the perfluoroalkyl vinyl ether is perfluoropropyl vinyl ether.

6. The fluorine-containing polymer according to claim 5, wherein the content of units derived from said perfluoropropyl vinyl ether based on all units is 11 mol % or more.

7. The fluorine-containing polymer according to any one of claims 1 to 3, further having units derived from hexafluoropropylene.

8. The fluoropolymer according to claim 7, wherein the content of said units derived from hexafluoropropylene based on all units is 18 mol % or more.

9. Contains a trifluoromethyl moiety; The fluorine-containing polymer according to any one of claims 1 to 8, wherein the content of the trifluoromethyl moiety is 0.1 mmol / g or more.

10. A resin film comprising the fluoropolymer according to any one of claims 1 to 9 as a material.

11. An optoelectronic device comprising the resin film according to claim 10.

Citation Information

Patent Citations

  • Water-repelling glass

    JP1996239242A

  • Production of water repellent coating film

    JP1997025559A

  • Thin film of oriented molecule

    JP1999001593A

  • Transparent composite conductor with high work function

    JP2009526351A

  • Fluorine-based surface treating agent and article treated with the same

    JP2015010209A